The Application of a Product Mix Linear Programming Model in Corporate Policy Making - Byrd, Jack; Moore, L. Ted (Management Science, 1978)
This paper reports a real-life application of linear programming to corporate policy making. The model used in the study was designed to analyze the company's marketing and production policies. The model structure is unique, incorporating features of product mix, sequencing and blending models. The model's structure is described as well as typical results it produced. The recommendations for corporate actions arising from the model are also explained. Recommendations were made to alter the existing corporate policies on brand proliferation and limited inventory levels. The product line has been reduced as a result of the study, and a policy decision to expand the inventory has been made. The process of implementation is sketched to provide a feeling for the difficulties involved in corporate policy making.